Maintaining Quality While Expanding Our Reach: Using Online Information Literacy Tutorials in the Sciences and Health Sciences - Matlin, Talitha; Lantzy, Tricia (Evidence Based Library and Information Practice, 2017)
Objective – This article aims to assess student achievement of higher-order information literacy learning outcomes from online tutorials as compared to in-person instruction in science and health science courses.Methods – Information literacy instruction via online tutorials or an in-person one-shot session was implemented in multiple sections of a biology (n=100) and a kinesiology course (n=54). After instruction, students in both instructional environments completed an identical library assignment to measure the achievement of higher-order learning outcomes and an anonymous student survey to measure the student experience of instruction.Results – The data collected from library assignments revealed no statistically significant differences between the two instructional groups in total assignment scores or scores on specific questions related to higher-order learning outcomes. Student survey results indicated the student experience is comparable between instruction groups in terms of clarity of instruction, student confidence in completing the course assignment after library instruction, and comfort in asking a librarian for help after instruction.Conclusions – This study demonstrates that it is possible to replace one-shot information literacy instruction sessions with asynchronous online tutorials with no significant reduction in student learning in undergraduate science and health science courses. Replacing in-person instruction with online tutorials will allow librarians at this university to reach a greater number of students and maintain contact with certain courses that are transitioning to completely online environments. While the creation of online tutorials is initially time-intensive, over time implementing online instruction could free up librarian time to allow for the strategic integration of information literacy instruction into other courses. Additional time savings could be realized by incorporating auto-grading into the online tutorials.